Design and Development of Urban Cultural and Creative Products with Segment Filling Insertion. Issue 1 (February 2021) - Fang, Jiahui; Ma, Yanxue; Li, Yuling; Wei, Yi; Zhang, Ruiyun; Wen, Run; Xue, Wenliang; Wu, Jianhua
Abstract: Known as the essential filling insertion technology of Kesi and Yunjin, the segment filling insertion can only be inherited by handicraftsman currently, which is threatened with extinction. In the study, automatic segment filling insertion technology was introduced, and applied to produce cultural and creative woven products with urban themes. What proposed in this paper can not only promote the digital innovation of the traditional weaving process, but also incorporate into the contemporary cultural creative products.